Microbe Profile: Streptomyces coelicolor: a burlesque of pigments and phenotypes - Nodwell, Justin R. (Microbiology (Reading), 2019)
The streptomycetes are soil-dwelling bacteria that are found in soil everywhere on Earth: the molecule geosmin, which they produce as part of their life cycle, is what gives soil its familiar ‘earthy’ smell. The species is best known for the production of biologically active small molecules called ‘natural products’. These molecules are the source of most of our antibiotics and anti-fungals, as well as many other drugs. The streptomycetes have a filamentous form rather than the more familiar rod-shaped spirochete and coccoid forms. They exhibit a complex life cycle and sporulation mechanism involving several differentiated cell types, each having specific roles in the colony life history. Streptomyces coelicolor is an important model system for this genus – research on this bacterium has provided foundational information for all of these fascinating processes.